Navigating Linguistic and Cultural Barriers: A Case Study of International Students in a Private Kazakhstani University - Kabdesheva, A. (MAQSUT NARIKBAYEV UNIVERSITY School of Liberal Arts. Astana, 2025)
During the past decades, Kazakhstani universities have implemented internationalization efforts to boost academic appeal and student enrollment from abroad. The successful integration process requires systems to overcome communication barriers that international students encounter. Universities have to offer high-quality, adaptive support services to remain competitive and attractive for foreign applicants. This study employed a qualitative case study design to explore international students’ experiences at a private university in Kazakhstan. The study focused on international students’ experiences at a private Kazakhstani university. The research aims to identify the primary language, cultural, psychological, and environmental obstacles that prevent effective communication and adaptation. The study analyses current university support systems from the intercultural adaptation conceptual framework to determine their practices. The research data obtained through semi-structured interviews with international students and university leadership demonstrated that students encounter limited availability of academic resources in their native language and insufficient emotional support and cultural understanding from faculty and administrators. The provided support programs remain formal in nature, failing to meet the genuine requirements of students. The university’s support initiatives for foreign students have been implemented, yet the research outcomes demonstrated the need for institutional changes in international student support approaches. The findings provide practical recommendations to universities seeking to enhance Kazakhstan’s educational position in the region while improving international student adaptation environments.
Keywords: higher education, international students, communication barriers, institutional support, cross-cultural adaptation, Kazakhstan